Review Jurnal : Faktor Pengaruh Hubungan Gagal Ginjal Akut Dan Covid-19 - Mally Ghinan Sholih; Munir Alinu Mulki; Asman Hitopik; Ibtisamah Haura; Madame Marselly Sebayang; Nurfirah Mubarok; Rachel Noveriachristie Balapadang; Rima Putri Ramadhani; Rifa Nur Alia (Jurnal Ilmiah Wahana Pendidikan, 2023)
COVID-19 is a disease caused by infection with the SARS-CoV-2 virus and has become a global pandemic outbreak because it is highly contagious and causes severe infections of the respiratory system. The SARS-CoV-2 virus causes infection primarily in the lungs and upper respiratory tract but can also infect other organs such as the brain, kidneys, intestines and liver. During the pandemic, many serious complications from COVID-19 were reported and one of them was acute kidney failure. Acute kidney failure is a condition where kidney dysfunction occurs quickly and suddenly. This study aims to investigate the factors that influence the relationship between acute kidney failure and COVID-19 infection. This research method begins with a literature search through the PubMed Identifier (PMID) database within a predetermined range of years and using the keywords pathophysiology, COVID-19, and acute kidney failure. The results of the review show that there are several factors that play a role in influencing the relationship between acute kidney failure and COVID-19 infection. Kidney damage in COVID-19 patients can occur due to a direct attack from the SARS-CoV-2 virus, the occurrence of a cytokine storm, or an indirect attack which can be caused by nephrotoxin exposure due to medical care given to the patient, secondary infection, or other factors. such as elderly and chronically ill patients. Based on the findings, it is known that there are risk factors, pathophysiological mechanisms, and patient medical care that can influence the relationship between acute kidney failure and COVID-19 infection. From the results of this analysis, it is hoped that the findings obtained can serve as a basis and guideline in the management of acute kidney failure as a complication of COVID-19.